2018
DOI: 10.21307/jofnem-2018-055
|View full text |Cite
|
Sign up to set email alerts
|

Effector gene vap1 based DGGE fingerprinting to assess variation within and among Heterodera schachtii populations

Abstract: Populations of beet cyst nematodes Heterodera schachtii vary in aggressiveness and virulence toward sugar beet varieties, but also in traits like host range, or decline rate in the field. Diversity of their essential pathogenicity gene vap1 is shaped by diversifying selection and gene flow. The authors developed a technique to study interpopulation variation and intra-population diversity and dynamics of H. schachtii based on the gene vap1. Degenerate primers were designed to amplify, clone, and sequence this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 33 publications
1
12
0
Order By: Relevance
“…Cai J L pointed out that a new multi-layer convolutional network model can be used in the model construction and connection prediction of large-scale knowledge graphs, which can build highly complex knowledge graphs based on its high parameter efficiency (Cai et al, 2019). Nuaima R H applied a new learning framework in the study of reasoning large-scale knowledge graphs (KG), which can construct knowledge graphs with continuous states in the KG vector space more accurately, diversely and efficiently (Nuaima et al, 2018). Shi J found that existing self-symptom detectors are far from meeting the needs of clinical decision support systems.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Cai J L pointed out that a new multi-layer convolutional network model can be used in the model construction and connection prediction of large-scale knowledge graphs, which can build highly complex knowledge graphs based on its high parameter efficiency (Cai et al, 2019). Nuaima R H applied a new learning framework in the study of reasoning large-scale knowledge graphs (KG), which can construct knowledge graphs with continuous states in the KG vector space more accurately, diversely and efficiently (Nuaima et al, 2018). Shi J found that existing self-symptom detectors are far from meeting the needs of clinical decision support systems.…”
Section: Literature Reviewmentioning
confidence: 99%
“…DNA was extracted from the pooled cysts using the lysis buffer method [23]. In brief, the volume of the lysis buffer was added to one volume of the prepared nematode suspension, and then incubated at 66 • C and 100 • C for two hours and 5 min, respectively.…”
Section: Radish Bioassaymentioning
confidence: 99%
“…The PCR-amplification of the effector gene vap1 from the nematode DNA was conducted using the primer pair HSvap244f/HSvap548r designed to amplify vap1 fragments of approximately 365 bp from the genomic DNA of H. schachtii populations [23]. The conditions for PCR reaction used the published protocol.…”
Section: Radish Bioassaymentioning
confidence: 99%
See 2 more Smart Citations